To Design a Fire Ball Extinguisher Launcher Attachment to Drone - Mohamad Rudi, Wan Muhammad 'Izzat Ruzain; Abd Rahim, Abd Khalil (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Drone technology are the future of various fields. Malaysia has announced the use ofmore drone technology as it can be used to create more than 100,000 jobopportunities for Malaysians. In 14 October 2021, drone technology will be going onfull throttle with the TPM Area 57. Area 57 provides infrastructures and facilities forUAS innovators and developers to test their technology as well as studying them.Moreover, other countries have already started their investments and research indrone tech which gives them more applications of drone in their jobs. For instance,firefighting. Countries like China, India and America has already started using drones for these operations which increases the percentages of survival thus gives more percentages to rescue and put out fire. Some of the product uses water and some uses fire extinguishing ball. This project is the design of fire extinguisher ball launcher as thenewest technology of this design was designed to only drop them from a higherground. Methods mentioned before, dropping the FEB could cause damage to thedrone us drones need to fly above the fire source thus causes updraft forces inflictedto the drone. These forces can case drone pilot to lose control which can result todrone crashes. The purpose of this design was to launch fire extinguishing ball to fire sources while being attached to the drone itself. Targeted objective was reached however, there were some difficulties faced that the design did not reach the full requirement made by customers.